An analysis of heat transfer inside the ice layer and solid wall during ice accretion. (October 2022) - Chen, Ningli; Yi, Xian; Wang, Qiang; Chai, Deling
Abstract: Heat transfer during ice accretion is a complex process that couples heat convection, drop impingement, evaporation, fusion, and heat conduction. However, in most numerical simulations of ice accretion in the literature, heat conduction in both the ice layer and the wall is neglected for simplification. This paper examines whether this approximation is acceptable by proposing a scheme for the calculation of the coupled heat transfer during ice accretion, including heat conduction inside both the ice layer and the solid wall. A glaze-ice scenario is used for the coupled heat transfer analysis, and the results show that latent heat generated during the freezing process is transferred to the ice and wall through conduction, raising their temperature above the incoming temperature. The heat conduction in surface tangent direction dominants in the solid wall while heat conduction in the normal direction dominants in the ice layer. The results also show that the heat transferred from the ice layer to the water film is negligible, meaning heat conduction in the ice layer and solid wall can be neglected, which, however, can cause relatively large errors at the upper and lower ice coverage limitations. Highlights: Proposed a method for calculation of the coupled heat transfer in ice accretion. The temperature of the ice and wall is above the incoming temperature. Tangent heat transfer in the ice layer along the surface is negligible. The heat transferred from the ice layer to the water film is negligible.